The comparison of postural balance in elderly active, sedentary and with vestibulopathy - Oliveira, Marcio Rogério de; Matos, Luana da Silva; Simon, Paula Thamirys Chaves; Jr, Rubens Alexandre da Silva; Costa, Viviane de Souza Pinho (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: To be sedentary and have any disease with regard to vestibular pathology can compromise the performance of the postural control and increases the risk of falls. Objective: This study aimed to compare the postural control of elderly active, sedentary and vestibular pathology. Methods: The sample consisted of 45 elderly separated according to their current health condition: elderly active, sedentary and with vestibulopathy. The postural balance tests were performed in bipedal support, eyes open and the variables measured by the force platform were the center of pressure and average speeds of postural sway in the directions, anteroposterior (A/P) and medial-lateral (M/L). Results: Elderly with vestibulopathy presented significantly poorer postural balance (P <0.05) that active and sedentary group, with large size effect: in mean d >0.80. Conclusion: Elderly with vestibulopathy have poor postural balance that elderly active and sedentary. These findings have any implications for programs of rehabilitation for vestibular disorders.